Treasures of the Thunder Dragon : a portrait of Bhutan - Ashi Dorji Wangmo Wangchuck, Queen, Consort of Jigme Singye Wangchuck, King of Bhutan. 1955 (New Delhi : Pengin Books India, 2012)
Author's memoir of travelogue with the historical and cultural description of Bhutan.
Includes index.
Keywords: Ashi Dorji Wangmo Wangchuck, -- Queen, Consort of Jigme Singye Wangchuck, King of Bhutan, -- 1955- -- Travel; Queens -- Travel -- Bhutan; Bhutan -- Description and travel